Effect of quenching on microstructure and wear‐resistance of Fe–10Cr–1.5B–2Al Alloy: Einfluss des Abschreckens auf die Gefügestruktur und den Verschleißwiderstand der Legierung Fe–10Cr–1, 5B–2Al. Issue 9 (14th September 2016) - Jiang, J.; Fu, H.; Zheng, L.; Shu‐Qi, G.; Yue, M.; Yong‐ping, L.
Abstract : Cast Fe–10Cr–1.5B–2Al alloy was quenched at different temperatures. The effects of quenching temperature on microstructure and hardness and wear‐resistance of Fe–10Cr–1.5B–2.0Al alloy were investigated by means of the optical microscopy, the scanning electron microscope, X‐ray diffraction, energy dispersive spectrometer, Vickers hardness and Rockwell hardness tester, and the MM‐200 block‐on‐ring wear testing machine under dry friction condition. The results indicate that the as‐cast microstructure of Fe–10Cr–1.5B–2.0Al alloy consists of ferrite, pearlite and netlike eutectics which are distributed in the grain boundary. The eutectics mainly include herringbone M2 B and chrysanthemum M7 (C, B)3 . The matrix gradually turns into single martensite with the increase of the quenching temperature. The type of borocarbides has no obvious change after quenching. The netlike boride almost totally fractures and transforms from the fish‐bone structure to the graininess. There is some retained austenite in the quenched structures when the quenching temperature is more than 1100 °C. When the quenching temperature is in a range of 1000 °C to 1100 °C, the hardness and wear resistance show a sharp increase with an increase of temperature, and show a slight decrease after surpassing 1100 °C.